2019
DOI: 10.1158/1055-9965.epi-18-1102
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Pathogenic Germline Variants in CDH1, BRCA2, CHEK2, PALB2, BRCA1, and TP53 in Sporadic Lobular Breast Cancer

Abstract: Background: Invasive lobular breast cancer (ILC) accounts for approximately 15% of invasive breast carcinomas and is commonly associated with lobular carcinoma in situ (LCIS). Both have been shown to have higher familial risks than the more common ductal cancers. However, there are little data on the prevalence of the known high and moderate penetrance breast cancer predisposition genes in ILC. The aim of this study was to assess the frequency of germline variants in CDH1, BRCA2, BRCA1, CHEK2, PALB2, and TP53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
(51 reference statements)
2
22
1
1
Order By: Relevance
“…Increasing researches reported that CDH1, BRCA2, and BRCA1 were susceptibility genes for BC ( Petridis et al, 2019 ) and around 60–70% of women with BRCA1 or BRCA2 gene mutations would be suffered with BC in her lifetime ( Antoniou et al, 2003 ). Besides, BRCA2 mutation carriers were more likely to develop brain metastases than non-carriers ( Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing researches reported that CDH1, BRCA2, and BRCA1 were susceptibility genes for BC ( Petridis et al, 2019 ) and around 60–70% of women with BRCA1 or BRCA2 gene mutations would be suffered with BC in her lifetime ( Antoniou et al, 2003 ). Besides, BRCA2 mutation carriers were more likely to develop brain metastases than non-carriers ( Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus many commercial gene panels for breast cancer hereditary predisposition include, in addition to TP53, the CDH1 tumour suppressor gene. Whilst germline CDH1 mutations have been described in 0.34% of lobular breast cancer cases [22], they are more commonly associated with diffuse gastric cancer, a diagnosis with a dismal prognosis and prophylactic gastrectomy being the main preventable measure. In view of the uncertainties around true penetrance in breast cancer and the real potential for psychological harm, CDH1 is not included in NHS England hereditary breast cancer panel testing, as was determined by the UK Cancer Genetics Group [23].…”
Section: Breast Cancer Gene Panel Testing and The Need For A Refined mentioning
confidence: 99%
“…BRCA1, BRCA2, PALB2 confer a high risk of developing breast cancer and are enriched in familial cases. Notably, lobular breast cancer (LBC) is less common as a proportion of breast cancers in women with BRCA1 PGVs compared to women without BRCA1 PGVs [3][4][5][6] As the main pathway to breast cancer is from basal progenitor cells leading to the predominant ductal triple negative breast cancer, this route excludes the predominantly estrogen receptor positive lobular cancer. However, individuals with BRCA2 PGVs have a similar proportion of LBC to women without BRCA2 PGVs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the association for the diffuse gastric cancer predisposition gene, CDH1, in lobular, rather than ductal breast cancer [9][10][11][12]. Petridis et al screened six genes for an association with LBC and found that variants in BRCA2, CHEK2, and PALB2 in addition to CDH1 were all enriched in women with lobular compared to ductal cancer [5].…”
Section: Introductionmentioning
confidence: 99%